2022
DOI: 10.3390/su14073843
|View full text |Cite
|
Sign up to set email alerts
|

Does ESG Performance Promote High-Quality Development of Enterprises in China? The Mediating Role of Innovation Input

Abstract: Environmental, Social and Governance (ESG) concept has internal consistency with the high-quality development of China’s economy theoretically, and implementing ESG concept is an important way to achieve sustainable economic development. However, whether ESG performance can promote the high-quality development from the perspective of micro enterprises is rarely studied. Thus, we explore the impact and mechanism of ESG performance on enterprises’ high-quality development. The empirical results indicate that goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 64 publications
0
42
0
Order By: Relevance
“…(1) research intensity, (2) Diversity, (3) board experience and (4) profitability. Ge, et al (2022) identify a mediating influence of innovative inputs on environmental, social and governance performance. The sub-sample results in Table 8 confirm the findings of Ge, et al (2022) and conclude that Shari'ah-compliant research-intensive firms have better environmental performance.…”
Section: [Please Insert Table 7 Here]mentioning
confidence: 99%
“…(1) research intensity, (2) Diversity, (3) board experience and (4) profitability. Ge, et al (2022) identify a mediating influence of innovative inputs on environmental, social and governance performance. The sub-sample results in Table 8 confirm the findings of Ge, et al (2022) and conclude that Shari'ah-compliant research-intensive firms have better environmental performance.…”
Section: [Please Insert Table 7 Here]mentioning
confidence: 99%
“…(L. Wang, et al, 2022) 1 . But some studies have proposed that corporate governance affects the improvement of firm value most, exceeds the effect of environmental and social responsibility (G. Ge, et al,2022) 8 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chouaibi, Chouaibi [11] and Xu, Imran [136] identified mediating role of green innovation on ESG and financial performance. Ge, Xiao [137] demonstrated that innovation input mediates the relationship between ESG and the high-quality development of Chinese enterprises. Yoo, Yeon [138] confirmed the mediating role of technology on CSR and corporate financial performance in the US hospitality industry.…”
Section: The Mediating Role Of Innovation On the Relationship Between...mentioning
confidence: 99%